The Effect of Investment Decisions, Dividend Policy, and Profitability on Firm Value in the Manufacturing Industry in West Java - Patriandari Patriandari; Efrinal Efrinal; Sari Mujiani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to provide empirical insight into the interaction of financial factors, investment decisions, dividend policy, and profitability and their effects on firm value using the Structural Equation Modeling with Partial Least Squares (SEM-PLS) approach. This quantitative study uses data from 150 manufacturing companies in West Java selected through stratified random sampling, with data collected through structured surveys and interviews with key decision makers. The results of the analysis show that investment decisions have a positive and significant effect on firm value, indicating that proper capital allocation can increase business value. Dividend policy shows a complex relationship with firm value, so a balanced dividend distribution strategy is needed. Profitability has a strong positive correlation with firm value, emphasizing the importance of maintaining profit sustainability. This research model is able to explain 65% of the variation in firm value, indicating the strength of the relationship between the variables analyzed. The practical implication of this study is the importance of financial strategy decision making in the manufacturing sector, especially in terms of investment and dividend policy. Companies are advised to implement a careful investment strategy, moderate dividend policy, and focus on profitability to increase market valuation. This study makes an original contribution by presenting empirical data from the under-researched manufacturing sector of West Java and presenting a comprehensive model that explains the key dynamics that determine firm value in the industry.